Hidradenitis suppurativa - current and promising non-surgical treatment - Baran, Natalia; Bogusz, Klaudia; Maksymowicz, Marcela; Bielak, Adriana; Nowak, Aleksandra; Cywka, Łucja; Szwed, Weronika; Nowak, Alicja; Machowiec, Piotr (Journal of Education, Health and Sport, 2023)
Introduction and purpose: Hidradenitis suppurativa (HS) also known as acne inversa is a chronic, inflammatory dermatosis with predilection to apocrine gland-rich regions. It is a multifactorial disease in which genetic and environmental factors play a key role. In this paper, we provide an overview of the current knowledge in most commonly used and emerging treatment options of HS. A brief description of the state of knowledge: The primary defect in HS pathophysiology involves follicular hyperkeratosis with occlusion of the pilosebaceous apparatus, followed by follicular rupture and immune responses. It typically develops after puberty with deep-seated painful nodules, abscesses, sinus tracts and scars. Due to the permanently painful, odorous lesions, hidradenitis suppurativa is one of the most distressing dermatological diseases with a substantial impact on patients’ quality of life. Inflammation in patients with HS is not limited to the skin but is systemic. Patients with HS frequently have significant comorbidities like metabolic syndrome, type 2 diabetes mellitus, spondyloarthropathy, inflammatory bowel disease and depression. Treatment is challenging and consists of pharmacological and surgical techniques, which must often be combined for best results. Materials and methods: A search was conducted using PubMed and GoogleScholar data bases. Articles were searched in English using the following key words: “hidradenitis suppurativa”, “acne invera”, “treatement”, “management”, “biological treatement”. Summary: Therapeutic options have rapidly evolved in the last decade and include the use of topical therapies, systemic antibiotics and a wide range of immunosuppressive medications such as anti-TNF-α biologics, but the number of therapies approved for HS is limited.